Occurrence of Hyacinth Macaw nesting sites in Sterculia apetala in the Pantanal Wetland, Brazil - Santos Júnior, Antônio; Tomas, Walfrido M.; Ishii, Iria H.; Guedes, Neiva M.R.; Hay, John D. (Gaia Scientia, 2007)
Manduvi tree, Sterculia apetala, provides critical habitat, hosting 94% of the threatened hyacinth macaw (Anodorhynchus hyacinthinus) nesting sites. We examined the probability of occurrence of nesting sites in Steculia trees and the population structure of this tree species at three sites in the Pantanal due to the increasing conversion of forest to pasture where S. apetala occurs, its populations may be under threat as well as the availability of nesting sites to the hyacinth macaw. A logistic model of the relationship between presence of macaw nests and tree diameter at breast height (DBH) showed that nests did not occur in trees smaller than 50 cm DBH and that most nests occurred in trees with DBH greater than 100 cm. The population structure indicates low recruitment in classes of DBH larger than 5 cm and a strong reduction in the occurrence of individuals greater than 50 cm DBH. Conservation priorities for the S. apetala and hyacinth macaw are presented.